Music Harmonizes Extracorporeal Shockwave Lithotripsy Experience by Reducing Anxiety and Pain – A Randomized Control Trial - Agha Zohaib, Adnan Siddiq, Salman El Khalid, Waqar Hassan, Mohammad Saleem, Wajahat Fareed (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out the role of listening to music during extracorporeal shockwave lithotripsy to reduce pain and anxiety during the procedure. Design: A randomised controlled trial. Place and Duration of Study: Lithotripsy department at The Kidney Centre Postgraduate Training Institute, Karachi, from January to July 2021. Methodology: One hundred ten patients were randomly assigned into two groups of fifty-five patients each; Group-M (first session of ESWL with music and second session without music) and Group-X (first session of ESWL without music and second session with music). Patients with the music group were provided headphones with soothing music throughout their procedure. Routine analgesic (intravenous nalbuphine 0.1mg/kg) was administered to patients as per treatment guidelines. Each patient received a total of 4000 shockwaves with energy levels varying from 11.45 to 13.1 kilovolts and frequency ranging between 2 to 3 Hertz. Patients filled out two questionnaires, Visual Analogue Scale (VAS) and State-Trait Anxiety Inventory (STAI). Baseline data for all patients was calculated and compared between the two groups. Data were analysed using IBM SPSS ver. 20. Results: Ninety-eight were males while twelve were females. Gender distribution between groups does not differ significantly (p = 0.862). The mean age in Group-M was 36.22 + 9.78 while in Group-X was 36.13 + 9.89 without any significant difference between groups (p = 0.422). BMI of Group-M patients (25.34 + 4.64) was not significantly different from Group-X (25.41 + 4.80) (p = 0.327). Median stone size of Group-M was 1.0 ; 0.30 while that of Group-X was 1.1; 0.40 (p=0.997). Stone laterality was not significantly different among the two groups (p = 0.961). The distribution of stone location among both groups was not significantly different from each other (p=0.949). In Group-M, first session patients (with music) had significantly lower median VAS score (2; 1) as compared to second session patients without music (4; 2), (p < 0.001). In Group-X, first session patients (without music) had significantly higher median VAS score (6; 1) as compared to second session patients with music (4; 2), (p < 0.001). Conclusion: Music therapy during ESWL sessions reduces both pain and anxiety and also improves overall compliance of stone disease patients by eradicating the fear of the procedure.